Evaluasi Komprehensif Konten Antibiotik di Instagram Reels: Implikasi untuk Edukasi dan Komunikasi Kesehatan Publik - Nafi'ah, Inti Kalun; Kusuma, Ikhwan Yuda; Maryanti, Nelly; Azizah, Azizah; Satyadewi, Putu Ratna Hari; Pratiwi, Amelia Candra; Susanto, Kharisma Evelyne Eka (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
Antimicrobial resistance remains a global health threat, with irrational antibiotic use being one of its main contributing factors. Social media platforms such as Instagram Reels now play an important role in public health communication, especially among younger audiences. This study aimed to evaluate the characteristics, quality, and reliability of antibiotic-related content on Instagram Reels through content analysis. A cross-sectional study was conducted on 100 videos selected using purposive sampling based on search results with the keyword “antibiotic use” over a two-week period in July 2025. Video quality was assessed using the Journal of the American Medical Association (JAMA) benchmark criteria and the Video Information and Quality Index (VIQI). The results showed that health professionals (50%) and health organizations (45%) were the main content creators, while influencers accounted for only 5%. The dominant themes included appropriate antibiotic use (55%) and resistance (38%), whereas self-medication (21%) and side effects (19%) were underrepresented, and no content addressed misinformation. Overall, video quality was moderate (VIQI-sum = 14.23), with high scores for authorship and currency but low scores for attribution and disclosure. Videos created by health professionals had significantly higher information quality than those by non-health influencers (p = 0.011). These findings highlight the potential of Instagram Reels as a medium for antibiotic education and emphasize the importance of healthcare professional involvement in ensuring evidence-based communication.